REGULASI ANTIMIKROBA SISTEM PROSPEKTIF (RASPRO): SISTEM TATA GUNA ANTIBIOTIK UNTUK KENDALI MUTU DAN KENDALI BIAYA DI RUMAH SAKIT SEBAGAI UPAYA MENURUNKAN BEBAN BPJS KESEHATAN - WIDYAWATI LEKOK; RONALD IRWANTO NATADIDJAJA; ANTI DHARMAYANTI (Media Bisnis, 2020)
According to various analyses, Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) is experiencing a significant deficit. Inefficiency in the use of drugs in health services, including prescribing and using antibiotics, creates a bigger burden for BPJS. In the term of these conditions, quality and cost control is necessary to be done. RASPRO is an antibiotic stewardship program that can be used as an alternative to increase the effectiveness of antibiotic quality and cost control as listed in PERMENKES 8/2015 concerning antibiotic resistance control as an effort to reduce BPJS costs.